Tialo Language Affix for Verb Marker - Ulinsa, Ulinsa; Marzuki, Abdul Gafur; Idris Patekkai; Fadila, Fadila; Deni Karsana; Tamrin, Tamrin (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The problems in this study are the types, meanings, and forms of affixes marking the Tialo language verbs. This study aims to describe the types, meanings, and forms of the Tialo language, including prefixes, suffixes, infixes, and confixes. The method used is a qualitative method. This study used the observing and speaking methods, with tapping techniques, proficient involvement techniques, proficient free observing techniques, fishing techniques, all-encompassing techniques, and note-taking techniques. The data analysis technique used is the distributional and equivalent method using the smallest element breakdown technique. Based on the results of research that has been carried out, it was found that affixes are markers for Tialo language verbs which include: Prefixes {moN-}, {non-}, {meN-}, {neN}, {poN-}, {peN-}, {in-}, and {te-}. {in-} infix. Suffixes {i-} and {a'a}. Confixes {moN-a'a} {noN-a'a}, {meN-a'a}, {meN-omo}, {nen-omo}, {poN-omo} and {moN-i}. The meaning of the affix markers in the Tialo language is going to take action, is taking action, has taken action, ordered, has taken action for others, and has finished taking action for others. Meanwhile, the affixes for the Tialo language consist of prefixes {mo-}, {no-}, and {me-}. {in-} infix. Suffixes {-i} and {a'a}. The confixes {mo-i}, {mo-a'a}, and {no-a'a} in the affix form of the Tialo language verb markers have changed and some have not changed.